Comparison of clinical and arthroscopic findings in meniscaltears - Kostov Hristijan; Kostova Elena (Sanamed, 2014)
Introduction: This study was conducted to compare the clinical and arthroscopic findings in lateral and medial meniscal tear injuries in order to assess the diagnostic significance of the clinical examinations findings. Patients and methods: All patients attending our clinic with knee pain from2009. to 2013. underwent systematic and thorough clinical assessment. From one hundred and three patients with knee problems in 40 were diagnosed LM (lateral meniscus) tears and in 45 MM (medial meniscus) tears arthroscopically. In this study meniscal tears were clinically diagnosed by positive McMurray and Apley test. All clinically diagnosed patients underwent diagnostic and therapeutic knee arthroscopy to assess the accuracy of clinical diagnosis. The accuracy, PPV, NPV, sensitivity and specificity were calculated based on clinical examinations and arthroscopic findings. Results: Identification of meniscal tears in our study was presented with 85% accuracy of 'McMurray' clinical examination test for LM tears and 80% accuracy for the MM tears, and for 'Apley' clinical examination test for LM tears was obtained with 73% accuracy and 63% accuracy for MM tears. Conclusion: According to our findings we can conclude that McMurry clinical examination test is more accurate for predicting i.e. diagnosing of meniscal tears. Contrary, Apley clinical examination test showed less accuracy for predicting i.e. diagnosing of meniscal tears.